An Improved Biogeography-Based Optimization for the Long-Term Carpooling Problem. Issue 10 (24th August 2021) - Kaleche, Rachid; Bendaoud, Zakaria; Bouamrane, Karim
ABSTRACT: The increasing number of vehicles on the road produces negative effects for health, the environment, quality of life, and the economy, among other areas. To address this problem, an important key is carpooling private vehicles from different homes to a common destination. This paper specifically addresses the long-term carpooling problem, which is an NP-complete problem. The proposed approach is a modified biogeography-based optimization metaheuristic, which is hybridized with a variable neighborhood search. Comparisons with efficient known approaches indicate the effectiveness of the proposed approach for large-scale long-term carpooling problems.